Transformation of the Concept of Maslahah in Sustainable Islamic Finance: a Hermeneutic Analysis of al-Ghazali's Thoughts and ash-Syatibi - Muhammad Zuardi; Ahmad Kholil; Amrin; Ishma Amelia (Universitas Muhammadiyah Surakarta, 2025)
Objective: This research aims to examine the transformation of the concept of maslahah in modern Islamic finance, especially in the shift from a normative approach in classical jurisprudence to a contextual approach in the contemporary financial system. Theoretical framework: The research is based on the thoughts of Al-Ghazali, who structured maslahah within the maqashid shariah paradigm (protection of religion, life, intellect, lineage, and property), and Asy-Syatibi, who introduced the flexible concept of maslahah mursalah. Literature review: involves an in-depth study of classical sources such as Al-Mustashfa and Al-Muwafaqatas well as contemporary literature on Islamic finance and sustainability. Methods: Using a hermeneutic approach, this study analyzes classical and modern texts through literature studies, referring to the works of Al-Ghazali (Al-Mustashfa) and Asy-Syatibi (Al-Muwafaqat) as well as various secondary literature. The results: The study indicate that the concept of maslahah has undergone significant development, from a text-based approach to a more flexible application in modern Islamic finance, such as in Islamic banking, green sukuk, and social-based financial instruments. This transformation strengthens the role of Islamic finance in supporting economic sustainability and the Sustainable Development Goals (SDGs). Implication: the reinforcement of Islamic finance as a value-based system capable of promoting inclusive and sustainable development. Novelty: This research lies in its hermeneutic reinterpretation of classical Islamic legal theory to justify and support its modern, sustainability-oriented applications.